2021
DOI: 10.1080/21655979.2021.2006951
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dendrobium officinale polysaccharides in repairing gastric mucosal injuries based on mitogen-activated protein kinases (MAPK) signaling pathway

Abstract: The present study aimed to investigate the protective effects and molecular mechanisms of Dendrobium officinale polysaccharides on gastric mucosal injuries. Following one week of continuous intragastric administration, a gastric mucosal injury model was established using intragastric administration of anhydrous ethanol. The area of gastric ulcer was measured, the contents of interleukin- 6 (IL-6), epidermal growth factor receptor (EGFR), and thyroid transcription factor 1 (TFF-1) in serum were detected by enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Liang et al ( 15 ) found that D. officinale polysaccharide (DOP-G-3) could reduce inflammatory damage, reduce colon pathological damage, and protect colon from dextran sulfate sodium (DSS)-induced colitis. Ma et al ( 79 ) found that D. officinale polysaccharide could reduce the expression of IL-6, Raf-2, MEK1, MEK2, and ERK by promoting the expression of EGFR and TFF-1 expression, thus reducing the level of inflammatory factors and protecting the gastric mucosa.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Liang et al ( 15 ) found that D. officinale polysaccharide (DOP-G-3) could reduce inflammatory damage, reduce colon pathological damage, and protect colon from dextran sulfate sodium (DSS)-induced colitis. Ma et al ( 79 ) found that D. officinale polysaccharide could reduce the expression of IL-6, Raf-2, MEK1, MEK2, and ERK by promoting the expression of EGFR and TFF-1 expression, thus reducing the level of inflammatory factors and protecting the gastric mucosa.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…In vivo: GU (-); EGFR and TFF1 (+); IL-6, Raf-2, MEK1, MEK2, and ERK1 (-); MAPK signaling pathway. In vitro: cell injury (-); EGFR and TFF1 (+); IL-6, Raf-2, MEK1, MEK2, and ERK1 (-); MAPK signaling pathway (Ma et al, 2022) (Continues)…”
Section: Chinese Iron Yammentioning
confidence: 99%
“…to screen gastroprotection action of polysaccharides, as an important mucosal defense barrier can be formed by these gastric epithelial cells (Laine et al, 2008). Polysaccharides from herbs (Ma et al, 2022;Qi et al, 2021;Qian et al, 2018 Meanwhile, as H. pylori is the dominating pathogen of gastric diseases, anti-H. pylori (Chandrashekar & Dharmesh, 2016;Srikanta et al, 2007) and H. pylori adhesion to gastric mucosa or cells (Inngjerdingen et al, 2014;Loke et al, 2007) have been utilized to evaluate the gastroprotective activities of some polysaccharides. Polysaccharides from herbs (Chandrashekar & Dharmesh, 2016;Harsha et al, 2016;Srikanta et al, 2007) and fungi (Zhu et al, 2014) could inhibit the growth of H. pylori with minimum inhibitory concentration (MIC) values ranging from 44 to 320 μg/ml.…”
Section: Gastroprotective Activity Of Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations